2010
DOI: 10.2174/138161210791033932
|View full text |Cite
|
Sign up to set email alerts
|

Nutlins and Ionizing Radiation in Cancer Therapy

Abstract: Radioresistance stands as a fundamental barrier that limits the effectiveness of radiotherapy in cancer treatment. Recent evidences suggest that radioresistance is due to tumour repopulation and involves several signalling pathways, including p53/MDM2 interaction. Ionizing radiation induces p53-dependent MDM2 gene transcription that, in turn, inhibits p53 transcriptional activity, favouring its nuclear export and stimulating its degradation. In light of the observation that in many human tumours the inadequate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 188 publications
0
36
0
Order By: Relevance
“…Many cytotoxic drugs (e.g. cisplatin) and irradiation can damage DNA and can activate wild-type p53 (14,15). In several reports, p53 wildtype cancer cells respond better to DNA-damaging therapeutics than p53-mutated or p53-null cancer cells due to activation of wild-type p53 growth-inhibitory pathways (16,17).…”
mentioning
confidence: 99%
“…Many cytotoxic drugs (e.g. cisplatin) and irradiation can damage DNA and can activate wild-type p53 (14,15). In several reports, p53 wildtype cancer cells respond better to DNA-damaging therapeutics than p53-mutated or p53-null cancer cells due to activation of wild-type p53 growth-inhibitory pathways (16,17).…”
mentioning
confidence: 99%
“…Many of these combinatorial therapies hold promise for future developments in the treatment of haematological malignancies since they may reduce excessive systemic toxicity toward normal cells and resistance of tumour cells after recurrent treatments. We and other authors have demonstrated that TRAIL-mediated cytotoxicity is increased by ionizing radiation and chemotherapy in both myeloid and erythroid leukaemia cell lines as well as in T lymphoma cell lines (Gong & Almasan, 2000;Di Pietro et al, 2001;Sabatini et al, 2004;Zauli et al, 2005;Caravatta et al, 2008;Impicciatore et al, 2010;Signore et al, 2011). Although an increasing number of drugs warrant further investigation as potential new strategies for the treatment of solid tumours or AML in combination with soluble rTRAIL (Suh et al, 2003), only in few cases the efficacy of the combined treatments has been proved in vivo and a general consensus on how chemotherapy and radiotherapy may synergize with TRAIL therapy is far to be reached (Russo et al, 2010).…”
Section: Novel Strategies To Overcome Trail Resistancementioning
confidence: 81%
“…The cytotoxic activity of TRAIL has been evaluated in haematological diseases by different groups of investigators, including our research group (Secchiero & Zauli, 2008;Impicciatore et al, 2010). Overall the activity of TRAIL as a single treatment in acute and chronic leukaemia is poor.…”
Section: Acute Myeloid Leukaemia (Aml)mentioning
confidence: 99%
See 2 more Smart Citations